2014
DOI: 10.1016/j.mgene.2014.04.003
|View full text |Cite
|
Sign up to set email alerts
|

G894T endothelial nitric oxide synthase polymorphism and ischemic stroke in Morocco

Abstract: Nitric oxide plays a major role in the regulation of cerebral blood flow and loss of its function leads to alteration of the vascular relaxation given its central role in the physiology of the vascular system. G894T eNOS polymorphism could have adverse effects on the expression and activity of endothelial nitric oxide synthase, which can result in functional impairment of the endothelium and contribute to the development of ischemic stroke in the different models of transmission.In this study, genotyping with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 33 publications
0
12
0
1
Order By: Relevance
“…Interestingly, this SNP was found to be associated with a higher risk towards stroke in other Asian populations such as in Indian population (Kumar et al 2016) and Taiwanese population (Shyu et al 2017), indicating that the association of this SNP with stroke risk is ethnic-dependent as the populations in Malaysia and Singapore consist of After stratification according to gender, we found that Malaysian males with the eNOS rs1799983-GT genotype had a significant increase risk towards stroke. However, studies based on other populations such as the Morocco population (Diakite et al 2014), Tunisian population (Saidi et al 2010) and German population (Berger et al 2007) had found that the association of this polymorphism with stroke was independent according to gender. The function of eNOS rs1799983 SNP has been well-studied but there are no studies reporting this SNP plays a different role in males and females.…”
Section: Discussionmentioning
confidence: 93%
“…Interestingly, this SNP was found to be associated with a higher risk towards stroke in other Asian populations such as in Indian population (Kumar et al 2016) and Taiwanese population (Shyu et al 2017), indicating that the association of this SNP with stroke risk is ethnic-dependent as the populations in Malaysia and Singapore consist of After stratification according to gender, we found that Malaysian males with the eNOS rs1799983-GT genotype had a significant increase risk towards stroke. However, studies based on other populations such as the Morocco population (Diakite et al 2014), Tunisian population (Saidi et al 2010) and German population (Berger et al 2007) had found that the association of this polymorphism with stroke was independent according to gender. The function of eNOS rs1799983 SNP has been well-studied but there are no studies reporting this SNP plays a different role in males and females.…”
Section: Discussionmentioning
confidence: 93%
“…A significant relationship between the T allele and TT genotype of the G894T polymorphism and ischemic stroke risk was found in Asians and north Indians, but not in Caucasians (Table 4) (3,6,10,17,18). In Morocco, Diakite et al reported a significant relationship between the G894T eNOS polymorphism and ischemic stroke in recessive, dominant, and codominant models ( Table 5) [16].…”
Section: G894t Polymorphismmentioning
confidence: 98%
“…Regarding its critical role in vascular system and blood flow regulation, NO-the main product of endothelial NOS enzyme-has been implicated in the occurrence of numerous pathologies, such as ischemic stroke (Diakite et al, 2014), HTA (Tang et al, 2008), renal disease (Aldámiz-Echevarría and Andrade, 2012), and cardiovascular diseases (Charalambos et al, 2006). According to the literature, studies exploring the association of G894T eNOS polymorphism with MI predisposition still remain inconclusive and results are contradictory (Luo et al, 2014).…”
Section: Enosmentioning
confidence: 99%
“…NO production-known for its role in regulation of blood pressure variability-is decreased and endothelial dysfunction occurs more often, leading to myocardial infarction development (Zhang et al, 2012;Song et al, 2013;Gong et al, 2012;Forstermann and Munzel, 2006;Franco et al, 2007;Diakite et al, 2014;Tang et al, 2008;Aldámiz-Echevarría and Andrade, 2012;Charalambos et al, 2006;Luo et al, 2014;Ben Ali et al, 2015;Casas et al, 2004;Veldman et al, 2002;Rankinen et al, 2000).…”
Section: Enosmentioning
confidence: 99%